The Moderation of Islamic ummah Seeing intentions in the concept of moderation (Journal of Human Sciences, 2020)
The most sources see the moderation as a dogmatic view means standing between religionisom and negligence which means making balance between the spiritual and material in the term of religiously, in addition to it being hereafter status for the Islamic Ummah to govern between nations on the Day of Resurrection. While we presented this paper; the moderation as a civilizational affairs that the ummah is commanded to lead the human scene in all the aspects of life, to become the patent giver to the rest of nations guided by the quran and Sunnah and what they hav from hints and signs to the increased places in the human product and this is what we understand from the meaning of the witness on the people and the witness of the messenger on the ummah.